Water management and supply - Cheremisinoff, Paul N. (New Jersey : Prentice-Hall, 1993)
This volume provides an overview of water, its properties, sources and uses in industry, commerce and transportation.
Contents : Water sources and uses Water quality and properties Chemical properties Examination of water Water supply purification Groundwater Industrial and commercial requirements Cooling waters
Includes bibliographical references.
Keywords: WATER QUALITY